Power line communications in practice [ - Carcelle, Xavier (Artech House telecommunications library, 2009)
Power line communications (PLC) is quickly taking root worldwide as an excellent alternative to Ethernet and Wi-Fi in private homes, buildings without Ethernet pre-wiring, and areas where Internet access is difficult. This title offers various things telecom engineers need to know about the technology, applications, equipment, and installation